An empirical study on the best planting medium used for the vegetative growth of cocoa seedlings / Muhammad Nabil Zafran Zakaria - Zakaria, Muhammad Nabil Zafran (Faculty of Plantation and Agrotechnology, 2018)
Theobroma cacao is the one of the world’s valuable crops, cultivated worldwide on 8.2 million hectares, grown in 58 countries annually. Growth of cocoa seedlings in nurseries using polybags is the recommended practice because the management of individual seedlings result in much vigour and improved capability of successful establishment. Nursery is the main place that can produce good quality of cocoa seedlings. This is attributed to minimized transplanting shock caused by the absence or reduced damage to the roots as compared to bare-root seedlings. The polybags also allow the nursery period to be prolonged until the environment is conducive for transplanting to the field. Planting media is the important component in order to produce a good quality of cocoa seedlings. The study was conducted to determine whether there is any significance difference on the growth performance of cocoa seedlings on the different type of media. The cocoa seedlings were planted in five types of media (Treatments) which are T1 (topsoil=control), T2 (1topsoil:1cocopeat), T3 (1topsoil:1sawdust), T4 (1topsoil:1sand) and T5 (1topsoil:1peatmoss). All these treatment effect can be observed through growth parameters which are stem girth, plant height, number of leaves and fresh and dry weight. The results showed that treatment 4 (1topsoil:1sand) has well in most of parameter and the lowest showed by treatment 3 (1topsoil:1sawdust). The evidence is the mixture between (1topsoil:1sand) are easy to found everywhere and the cost are also very low and there are no burden to small farmer afford it to start their planting activities.